Pengaruh Model Pembelajaran Kooperatif TPS Terhadap Keterampilan Komunikasi Matematis Siswa Kelas III SD - Febriyani, Febi; Isrok’atun, Isrok’atun; Irawati, Riana (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the influence of the Think Pair Share (TPS) cooperative learning model on the mathematical communication skills of elementary school students. This study uses a quasi-experimental method and a pretest-posttest group design. The population of this study is all students at SDN Gudang Kopi Sumedang, while the sample of this study is 31 students taken by cluster random sampling technique. Data is collected through written tests and observations during the learning process. The data produced was analyzed in a qualitative descriptive manner. The results showed that students' mathematical communication skills improved after learning with the TPS model. The average pretest score was 54.8, which increased to 80.3 in the posttest, with a gain value of 0.67, categorized as moderate. Observations also indicated that students were more active when working individually, discussing with a partner, and sharing discussion results in front of the class. In conclusion, the TPS learning model was proven effective in enhancing students' mathematical communication skills. This model can be an option for teachers to create interactive learning and actively engage students, particularly in mathematics learning at the elementary school level.